Plan de negocios para la creación y puesta en marcha de una empresa avícola en el municipio de la Unión-Sucre “Pavicola Sabaneta s.a.s” (2018)
This report is the result of a market study carried out in the municipality of La Unión and San Marcos of the department of Sucre, where the opportunity to create and start a poultry business was identified, given that these municipalities do not count with companies dedicated to the poultry sector, therefore the production and commercialization of broilers is offered by small producers that can not supply the local market, therefore the merchants are obliged to obtain the product in other remote municipalities, which they only produce high cost.